State-Business Partnership in Modern Conditions: Prospects for Transformation - V. A. Plotnikov (Управленческое консультирование)
The complexity of the economy and the increase in uncertainty, as well as the need to solve ambitious tasks aimed at achieving strategic national development goals, force us to search for new forms and mechanisms for starting long-term economic growth. One such mechanism is public-private partnership, understood in the article in a broad sense, as an extensive set of forms of mutually benefcial interaction between the state and business. The article analyses the prerequisites of intensifying partnership in the modern Russian economy and assesses the directions of its transformation.